2017
DOI: 10.1159/000471807
|View full text |Cite
|
Sign up to set email alerts
|

Role of Albumin in Growth Inhibition in Hepatocellular Carcinoma

Abstract: Objective: Levels of serum albumin have recently emerged, together with C-reactive protein, as an important prognostic indicator for hepatocellular carcinoma (HCC). It has recently been reported that larger HCCs are associated with lower albumin levels. However, the albumin-mediated growth decrease has yet to be determined. Methods: We examined a large HCC cohort and then by direct exposure of HCC cells in vitro, the relationship of albumin levels to HCC growth. Results: We found that patients with lower album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 24 publications
(24 reference statements)
1
73
1
Order By: Relevance
“…Studies have shown that serum albumin levels have prognostic significance in HCC, with lower serum albumin levels having significantly larger maximum tumor diameters. [24][25][26] In fact, serum albumin level is already being used as a criterion for the HCC staging systems.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Studies have shown that serum albumin levels have prognostic significance in HCC, with lower serum albumin levels having significantly larger maximum tumor diameters. [24][25][26] In fact, serum albumin level is already being used as a criterion for the HCC staging systems.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Although, the effects of albumin on the proliferation of hepatocellular carcinoma cells have been previously studied, the outcomes of those studies are debatable. They argued that albumin inhibits tumour evidenced by its increased levels correlating with cancer remission and addition of albumin to serum starved hepatoma cells caused G1 arrest (Nojiri & Joh, 2014;Bağırsakçı et al, 2017). It is worth noting that serum is essential for hepatocellular carcinoma growth (Zhuge & Cederbaum, 2006;Liang et al, 2013) whereas serum starvation is routinely carried out to arrest cells in G1 phase (Davis, Ho & Dowdy, 2001;Langan, Rodgers & Chou, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation was evaluated through changes in cell counts and cell cycle analysis whereas cell death was measured by analysing apoptotic DNA fragmentation and membrane permeabilization. Similar studies have been performed on the HepG2 hepatocellular carcinoma parent clone demonstrating that albumin prevents proliferation (Nojiri & Joh, 2014;Bağırsakçı et al, 2017a). In this study, the experiments were carried out on the HepG2/C3A subclone and were contradictory to these earlier findings.…”
Section: Introductionmentioning
confidence: 51%
“…Although, the effects of albumin on the cell cycle of hepatocellular carcinoma cells have been previously studied, the outcomes of those studies are debatable. They argued that albumin inhibits tumour evidenced by its increased levels correlating with cancer remission and addition of albumin to serum starved hepatoma cells caused G1 arrest (Nojiri & Joh, 2014;Bağırsakçı et al, 2017b). It is worth noting that serum is essential for hepatocellular carcinoma growth (Zhuge & Cederbaum, 2006;Liang et al, 2013) whereas serum starvation is routinely carried out to arrest cells in G1 phase (Davis, Ho & Dowdy, 2001;Langan, Rodgers & Chou, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation